Time from emerging heart failure symptoms to cardiac resynchronisation therapy: impact on clinical response. Issue 5 (4th October 2012) - Verbrugge, Frederik Hendrik; Dupont, Matthias; Vercammen, Jan; Jacobs, Linda; Verhaert, David; Vandervoort, Pieter; Tang, W H Wilson; Mullens, Wilfried
Abstract : Objective: To investigate whether time from onset of heart failure signs and/or symptoms (ie, progression to stage C/D heart failure) until implantation affects reverse remodelling and clinical outcome after cardiac resynchronisation therapy (CRT). Design: Cohort study of consecutive CRT patients, implanted between 1 October 2008 and 30 April 2011. Setting: Single tertiary care centre (Ziekenhuis Oost-Limburg, Genk, Belgium). Patients: Consecutive CRT patients (n=172; 71±9 years), stratified into tertiles according to the time since first heart failure signs and/or symptoms at implantation. Main outcome measures: Change in left ventricular dimensions, New York Heart Association (NYHA) functional class and freedom from all-cause mortality or heart failure admission. Results: Baseline renal function was better in patients implanted earlier after emerging heart failure symptoms (estimated glomerular filtration rate=73±20 vs 63±23 vs 58±26 ml/min/1.73 m 2 for tertiles, respectively). After 6 months, decreases in left ventricular end-diastolic/systolic diameter and improvement in NYHA functional class were similar among tertiles. Freedom from all-cause mortality or heart failure admission was better in patients with early implantation (p value=0.042). However, this was not the case in patients with preserved renal function (p value=0.794). Death from progressive heart failure was significantly more frequent in patients implanted later in their disease course. Conclusions: Reverse left ventricular remodelling after CRT is not affected by the duration of heart failure. However, clinical outcome is better in patients implanted earlier in their disease course, which probably relates to better renal preservation.